Disaggregate income and wealth effects in the largest euro area countries - Gabe de Bondt; Arne Gieseck; Pablo Herrero; Zivile Zekaite (European Central Bank (ECB), 2019)
This study extends a thick modelling tool for aggregated euro area real private consumption of de Bondt et al. (2019) to the four largest euro area countries. The suite of error correction models performs well in and out of sample. The ranges and averages of estimated elasticities are, however, sensitive to the exact model specification. We also show that decomposing disposable income into labour, property and transfer income is essential for understanding and forecasting consumption. Finally, substantial crosscountry heterogeneity in marginal propensities to consume out of income and wealth components calls for caution when interpreting aggregate euro area developments.
Keywords: C53; D12; E21; E27; 330; private consumption; income; wealth; thick modelling